2007
DOI: 10.1249/mss.0b013e31812e5294
|View full text |Cite
|
Sign up to set email alerts
|

Regular Physical Activity Influences Plasma Ghrelin Concentration in Adolescent Girls

Abstract: Regular physical activity influences plasma ghrelin concentrations in girls with different pubertal maturation levels. Plasma IGF-I concentration seems to be the main determinant of circulating ghrelin in healthy, normal-weight adolescent girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 32 publications
1
15
2
Order By: Relevance
“…None of the participants took medications or had a history of endocrine, metabolic, or kidney diseases. Throughout the study, no restrictions were placed on dietary intake and all subjects consumed their ordinary everyday diet (6) . The study was approved by the Medical Ethics Committee of the University of Tartu in Estonia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the participants took medications or had a history of endocrine, metabolic, or kidney diseases. Throughout the study, no restrictions were placed on dietary intake and all subjects consumed their ordinary everyday diet (6) . The study was approved by the Medical Ethics Committee of the University of Tartu in Estonia.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, biological age and main anthropometric parameters were assessed. The fi rst measurement session was conducted during the early follicular phase of the menstrual cycle in menstruating girls (6,23) . The second measurement session consisted of body composition assessment by dual-energy Pubertal development of the participants was assessed based on self-assessment using an illustrated questionnaire of pubertal stages according to the Tanner classifi cation method (24) .…”
Section: Methodsmentioning
confidence: 99%
“…Ghrelin stimulates short-term food intake, promotes gastric emptying, and regulates body weight. In patients with anorexia or post-bariatric surgery, profound changes in plasma ghrelin levels were found, suggesting that it is an important hormone in the regulation of body weight (Gaddipati et al 2006;Jürimäe et al 2007). Studies on the effects of acute or chronic exercise showed that high-intensity exercise could lower plasma ghrelin levels in rats (Ghanbari-Niaki et al 2008;Wang et al 2008;GhanbariNiaki et al 2009).…”
mentioning
confidence: 99%
“…All participants were free from present or past diseases known to affect skeletal metabolism, and none of the girls were receiving medications known to affect bone. Throughout the study period, no restrictions were placed on dietary intake and participants consumed their usual everyday diet [4,23]. …”
Section: Methodsmentioning
confidence: 99%
“…The participants were given photographs, figures and descriptions of breast and pubic hair development stages and asked to choose the one which most accurately reflected their appearance. Pubertal development according to the method of Tanner, which uses self-assessment of breast and pubic hair stages in girls, has been validated previously [25,26] and was used in our previous studies with girls [4,6,18,23]. All girls in this study were in Tanner stage 1.…”
Section: Methodsmentioning
confidence: 99%